Worker rights in collective bargaining - Benjamin W. Arold; Elliott Ash; William Bentley MacLeod; Suresh Naidu (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Collective bargaining agreements (CBAs) specify the contractual rights of unionized workers, but their full legal content has not yet been analyzed by economists. This paper develops novel natural language methods to analyze the empirical determinants and economic value of these rights using a new collection of 30,000 CBAs from Canada in the period 1986-2015. We parse legally binding rights (e.g., "workers shall receive...") and obligations (e.g., "the employer shall provide. ..") from contract text, and validate our measures through evaluation of clause pairs and comparison to firm surveys on HR practices. Using timevarying province-level variation in labor income tax rates, we find that higher taxes increase the share of worker-rights clauses while reducing pre-tax wages in unionized firms, consistent with a substitution effect away from taxed wages toward untaxed rights. Further, an exogenous increase in the value of outside options (from a leave-one-out instrument for labor demand) increases the share of worker rights clauses in CBAs. Combining the regression estimates, we infer that a one-standard-deviation increase in worker rights is valued at about 5.7% of wages.
Keywords: J32; J52; K31; H24; 330; worker rights; collective bargaining; natural language processing; employment